2016
DOI: 10.1016/j.dadm.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel diagnostic cerebrospinal fluid biomarkers for pathologic subtypes of frontotemporal dementia identified by proteomics

Abstract: IntroductionReliable cerebrospinal fluid (CSF) biomarkers enabling identification of frontotemporal dementia (FTD) and its pathologic subtypes are lacking.MethodsUnbiased high-resolution mass spectrometry–based proteomics was applied on CSF of FTD patients with TAR DNA-binding protein 43 (TDP-43, FTD-TDP, n = 12) or tau pathology (FTD-tau, n = 8), and individuals with subjective memory complaints (SMC, n = 10). Validation was performed by applying enzyme-linked immunosorbent assay (ELISA) or enzymatic assays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 52 publications
8
70
1
Order By: Relevance
“…This reinforces the notion that coincident pathologies, comorbid AD in this case, have an impact on CSF biomarkers 9 18 26. We also found that, in agreement with another study,27 YKL-40 in FTLD-Tau is elevated compared with AD and controls.…”
Section: Discussionsupporting
confidence: 93%
“…This reinforces the notion that coincident pathologies, comorbid AD in this case, have an impact on CSF biomarkers 9 18 26. We also found that, in agreement with another study,27 YKL-40 in FTLD-Tau is elevated compared with AD and controls.…”
Section: Discussionsupporting
confidence: 93%
“…The CSF YKL40 levels were 1.4 fold higher in the probable/definite bvFTD group compared to those in the primary psychiatric disorders. Of note, although the levels of NfL and YKL40 in the group of psychiatric disorders were lower than in bvFTD, they were higher than levels described in control subjects, which are typically in the range of 254-365 pg/mL for CSF NfL [12,15,35] and around 200 ng/mL for CSF YKL40 [8,36].…”
Section: Levels Of Csf Biomarkersmentioning
confidence: 56%
“…YKL-40 was measured with the MicroVue ELISA from Quidel (USA) 20. GFAP in CSF was determined with an ELISA from BioVendor (Czech Republic) and GFAP in blood was measured with the Simoa GFAP Discovery Kit (Quanterix, USA).…”
Section: Methodsmentioning
confidence: 99%